2011
DOI: 10.4049/jimmunol.1001135
|View full text |Cite
|
Sign up to set email alerts
|

Gp130-Dependent Astrocytic Survival Is Critical for the Control of Autoimmune Central Nervous System Inflammation

Abstract: Astrocytes are activated in experimental autoimmune encephalomyelitis (EAE) and have been suggested to either aggravate or ameliorate EAE. However, the mechanisms leading to an adverse or protective effect of astrocytes on the course of EAE are incompletely understood. To gain insight into the astrocyte-specific function of gp130 in EAE, we immunized mice lacking cell surface expression of gp130, the signal-transducing receptor for cytokines of the IL-6 family, with myelin oligodendrocyte glycoprotein35–55 pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 57 publications
7
87
0
Order By: Relevance
“…We hypothesize that astrocytes, which constitutively express FasL, may play a key role given that FasL-expressing astrocytes are in intimate contact with apoptotic T cells in EAE and can induce apoptosis of activated CD4 + T cells in vitro [21,22]. Consistently, our previous study also demonstrated that increased apoptosis of gp130-deficient astrocytes exacerbated EAE, partially due to an impaired elimination of CD4 + T cells from the CNS [23]. However, in vivo evidence confirming that astrocytic FasL is involved in the induction of CD4 + T-cell apoptosis in EAE is still lacking.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…We hypothesize that astrocytes, which constitutively express FasL, may play a key role given that FasL-expressing astrocytes are in intimate contact with apoptotic T cells in EAE and can induce apoptosis of activated CD4 + T cells in vitro [21,22]. Consistently, our previous study also demonstrated that increased apoptosis of gp130-deficient astrocytes exacerbated EAE, partially due to an impaired elimination of CD4 + T cells from the CNS [23]. However, in vivo evidence confirming that astrocytic FasL is involved in the induction of CD4 + T-cell apoptosis in EAE is still lacking.…”
Section: Introductionsupporting
confidence: 71%
“…The kinetics of disease and intraspinal CD4 + T-cell numbers indicate that FasL-dependent elimination of CD4 + T cells in EAE plays a particularly protective role in the recovery phase. Noteworthy, the more severe EAE of GFAP-Cre FasL fl/fl mice cannot be attributed to the GFAP-Cre transgene, since C57BL/6 GFAPCre mice without a loxP-flanked gene develop the same course of EAE as compared to WT mice [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of estrogen receptor-a, but not estrogen receptor-b, selectively from astrocytes diminishes the antiinflammatory and neuroprotective effects of estrogen on autoimmune inflammation (Spence et al 2011(Spence et al , 2013. In contrast, deletion of STAT3 or its associated membrane receptor GP130, markedly increases the spread of inflammation after traumatic injury, autoimmune disease, or infection (Okada et al 2006;Drogemuller et al 2008;Herrmann et al 2008;Haroon et al 2011;Wanner et al 2013). Deletion of YLK-40/BRP-39, an astrocyte produced anti-inflammatory protein, exacerbates autoimmune disease in mice (Bonneh-Barkay et al 2012).…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%